Short Communication: Prolactin and x-collagen genes polymorphism in Central Javanese local ducks, Indonesia - R Susanti; Ari Yuniastuti (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Susanti R, Yuniastuti A. 2020. Short Communication: Prolactin and x-collagen genes polymorphism in Central Javanese local ducks, Indonesia. Biodiversitas 21: 605-610. Genetic conservation is an effective approach to preserve unique and protected species in Indonesia, including indigenous duck (Anas platyrhynchos Linnaeus, 1758). One of the most important things is an identification effort by studying genetic characteristics to support genetic resource conservation programs. This study aim was to analyze the genetic polymorphisms of Central Javanese local duck based on prolactin (PRL) and collagen-x (COLX) genes. A total of 35 local ducks in Central Java was collected as samples, the duck’s calamus feathers were taken for tissue DNA isolation. Polymorphism analysis of PRL and COLX genes were performed using single nucleotide polymorphism (SNP) markers and PCR-RFLP method. The amplicons were then digested with DraI restriction enzyme (AhaIII) (5'TTT/ AAA) for PRL gene, and HaeIII (BsuRI) enzyme (5'GG/ CC-3 ') for COLX gene. The genotype was determined based on RFLP PCR amplicon band results from each target gene. For each gene, data on genotype frequencies, allele frequencies, expected heterozygosities (HE), and Hardy-Weinberg equilibrium were analyzed using PopGene32 software. Based on the PRL gene, there were 25 ducks (71.43%) with BB genotype and 10 ducks (28.57%) with AB genotype. While based on the COLX gene, as many as 25 ducks (71.43%) had TT genotypes, 9 ducks (25.71%) had TC types and 1 duck (1.86%) had CC types. Both PRL and COLX genotypes were clustered the Central Javanese local ducks into 5 haplotypes (A-E). The high allele frequency has belonged to B allele (85.71%) of the PRL gene and T allele (84.25%) of the COLX gene that showed high egg production and quality. Allele B (PRL gene) and T allele (COLX gene) could be predicted as weight eggs’ alleles marker.